Revisit Intention at Halal Tourism Destination - Yustina Chrismardani; Triana Setiyarini; Evaliati Amaniyah (Dinasti International Journal of Economics, Finance & Accounting, 2025)
More studies are needed to reveal the effect of halal tourism, tourist satisfaction and revisit intention in a tourist destination. Consequently, this research will show: (1) the direct relationship between halal tourism and satisfaction; (2) the relationship between halal tourism and revisit intention; (3) the relationship between satisfaction and revisit intention; and (4) the role of tourist satisfaction in mediating the relationship between halal tourism and revisit intention. 200 visitors who had visited tourism sites in Sumenep Regency were the subjects of this study, which used the purposive sample technique. The data was analyzed using SEM-PLS. It was discovered that tourist satisfaction is directly impacted by halal tourism. The revisit intention is directly impacted by satisfaction, while the indirect impact of halal tourism on the revisit intention is mediated by satisfaction.